The Contribution of the Edmodo-Based Group Investigation Type Learning Cooperative Learning Model Assisted by the Learning Management System (LMS) in Improving the Historical Thinking Skills of History Teacher Prospective Students - Yulia, Sofiani; Kurniawan Shavab, Oka Agus (Indonesian Journal of History Education, 2021)
The organizers carried out at the Siliwangi University History Education department at the time the professor of 2017 showed that their ability to think historically was still not optimal. This is part of the research results, which show that the index of historical thinking averages 53.6%. This study aimed to study various cooperative learning models of inquiry group type assisted by a Learning Management System (LMS) developed to improve the historical thinking skills of prospective history teachers. The research method is classroom action research. The research results in the first cycle showed that the index of historical thinking averaged 70.4%, and in the second cycle, the average historical result was 82.4%. Based on the results in the first and second cycles, using the investigative group learning model and Edmodo learning media can improve students' historical thinking.